2021
DOI: 10.1136/gutjnl-2021-325210
|View full text |Cite
|
Sign up to set email alerts
|

British Society of Gastroenterology guidelines for the management of iron deficiency anaemia in adults

Abstract: Iron deficiency anaemia (IDA) is a major cause of morbidity and burden of disease worldwide. It can generally be diagnosed by blood testing and remedied by iron replacement therapy (IRT) using the oral or intravenous route. The many causes of iron deficiency include poor dietary intake and malabsorption of dietary iron, as well as a number of significant gastrointestinal (GI) pathologies. Because blood is iron-rich it can result from chronic blood loss, and this is a common mechanism underlying the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
167
1
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(185 citation statements)
references
References 209 publications
(196 reference statements)
4
167
1
13
Order By: Relevance
“…An easy-to-use oral iron therapy with good absorption and low risk of gastrointestinal adverse events would minimize the burden of treatment on patients requiring long-term iron replacement. Various alternatives to oral ferrous iron formulations have been developed, including polysaccharide-ferric iron complexes, sucrosomial iron, sodium feredate, ferric citrate, and ferric maltol [27,[45][46][47].…”
Section: Iron Replacement Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…An easy-to-use oral iron therapy with good absorption and low risk of gastrointestinal adverse events would minimize the burden of treatment on patients requiring long-term iron replacement. Various alternatives to oral ferrous iron formulations have been developed, including polysaccharide-ferric iron complexes, sucrosomial iron, sodium feredate, ferric citrate, and ferric maltol [27,[45][46][47].…”
Section: Iron Replacement Therapymentioning
confidence: 99%
“…To date, ferric maltol has been assessed in almost 750 adults and adolescents (661 in clinical trials and 87 in real-world studies) with a range of underlying conditions, including IBD, CKD, and pulmonary hypertension. The clinical trials were designed, as far as possible, to reflect the real-world settings in which ferric maltol will be used, with primary endpoints at 12 or 16 weeks followed by longer-term maintenance treatment in line with recommended treatment durations for oral iron therapies and current understanding of the time required for physiologic restoration of iron stores [45,[88][89][90][91]. A further phase III study is being planned in infants and children (age range 1 month to 17 years) with IBD and irondeficiency anemia, which will use an oral suspension currently under investigation [92].…”
Section: Review Of the Evidence And Clinical Implicationsmentioning
confidence: 99%
“…About 5–12% of healthy premenopausal women have IDA, which is attributed to inadequate dietary intake, menstrual blood loss, pregnancy, and breastfeeding [ 27 , 28 ]. In premenopausal women, the prevalence of GI malignancy is low and bidirectional endoscopy is not generally recommended [ 29 ]. However, premenopausal women sometimes develop GI tract cancers or benign bleeding lesions such as peptic ulcers.…”
Section: Gastrointestinal Tract Evaluation Of Patients With Iron Deficiency Anemiamentioning
confidence: 99%
“…However, premenopausal women sometimes develop GI tract cancers or benign bleeding lesions such as peptic ulcers. Therefore, GI investigation of premenopausal women with IDA is justified, particularly in patients with recurrent IDA, symptoms, or a family history of GI malignancy [ 7 , 29 ]. In addition, studies have reported a high frequency of upper GI and colorectal cancers in premenopausal women [ 30 , 31 ].…”
Section: Gastrointestinal Tract Evaluation Of Patients With Iron Deficiency Anemiamentioning
confidence: 99%
See 1 more Smart Citation